A kid's dream - Pritchard, Cody.; Child Writes Project; Eidsvold State School Writers Group (Toowoomba, Qld. : Boogie Books, 2011)
"Sometimes even the most enthusiastic soccer players can't find all their gear, even on Grand Final Day! Often, sports gear is not the only thing forgotten..."--Back cover.
"Eidsvold State School Writers Group ... Child Writes"--T.p. verso.
For children.
Keywords: Soccer players -- Juvenile fiction; Lost articles -- Juvenile fiction; Soccer stories, English -- Australia; Australian